Expert consensus on a standardised definition and severity classification for adverse events associated with spinal and peripheral joint manipulation and mobilisation: protocol for an international e-Delphi study - Nicola R Heneghan; Katherine A Pohlman; Martha Funabashi; Lindsay M Gorrell; Stacie A Salsbury; Andrea Bergna (BMJ Open)
Introduction Spinal and peripheral joint manipulation (SMT) and mobilisation (MOB) are widely used and recommended in the best practice guidelines for managing musculoskeletal conditions. Although adverse events (AEs) have been reported following these interventions, a clear definition and classification system for AEs remains unsettled. With many professionals using SMT and MOB, establishing consensus on a definition and classification system is needed to assist with the assimilation of AEs data across professions and to inform research priorities to optimise safety in clinical practice.Methods and analysis This international multidisciplinary electronic Delphi study protocol is informed by a scoping review and in accordance with the ‘Guidance on Conduction and Reporting Delphi Studies’. With oversight from an expert steering committee, the study comprises three rounds using online questionnaires. Experts in manual therapy and patient safety meeting strict eligibility criteria from the following fields will be invited to participate: clinical, medical and legal practice, health records, regulatory bodies, researchers and patients. Round 1 will include open-ended questions on participants’ working definition and/or understanding of AEs following SMT and MOB and their severity classification. In round 2, participants will rate their level of agreement with statements generated from round 1 and our scoping review. In round 3, participants will rerate their agreement with statements achieving consensus in round 2. Statements reaching consensus must meet the a priori criteria, as determined by descriptive analysis. Inferential statistics will be used to evaluate agreement between participants and stability of responses between rounds. Statements achieving consensus in round 3 will provide an expert-derived definition and classification system for AEs following SMT and MOB.Ethics and dissemination This study was approved by the Canadian Memorial Chiropractic College Research Ethics Board and deemed exempt by Parker University’s Institutional Review Board. Results will be disseminated through scientific, professional and educational reports, publications and presentations.